Are new German postal providers successful? Empirical evidence based on unique survey data - Toufic M. El Masri (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
In order to investigate firm survival and the potential for competition in the German postal market, I analyzed key success determinants of market leader competitors. The analysis is based on eight 2011 case studies, in which I conducted in-depth interviews during on-site visits to various postal firms. The analysis is further supported by unique data stemming from a survey I conducted in 2010 for the German postal market. In general, I find that there are possibilities for smaller private firms to succeed and survive in the market despite the natural monopoly occurring within the postal industry. The success of these firms is often based on specialization, cooperation and combining the postal business with another business, such as publishing.
Keywords: D24; L51; L97; L22; 330; Competition; Firm Survival; Germany; Postal Sector; Success